Vaccines expert consult - Plotkin, Stanley A.; Orenstein, Walter A.; Offit, Paul A. (Elsevier, 2013)
A guide to the enhancement of the well-being of our world. It offers a coverage of every aspect of vaccination, from the development of each vaccine to its use in reducing disease.